Spatial characterization of compaction in agricultural land in CIAT, Colombia - Becerra, Carolina (2005)
During 2001, the compaction of vertisols, molisols and alfisols were determinated using patterns of punctual krigging of geostatystics and the overlapping technique of GIS-Arcview, based on five physical characteristics: gravimetric soils moisture, bulk density, cone penetration resistance. Additionally the content of organic matter content and texture, were determinated on field and laboratory at two depths: 2,5 cm and a depth between 10 and 30 cm. The compaction phenomenon was determinated by direct relations between soil moisture and density, soil moisture and cone penetration resistance, while inverse relations imply slight compaction or non compaction. The organic matter and texture determinated on laboratory, they influenced the contents of soil moisture, bulk density and cone penetration resistance, establishing interrelations that explain soil behavior as an effect of tillage methods. The areas of moderate compaction represents more than 60& of sampling area; slight compaction and non compaction areas represents less than 40%.